Responsiveness of restaurateurs towards the implementation of environment-friendly practices - Ismail, Anida; Kassim, Azilah; Zahari, Mohd Salehuddin (Centre for Tourism & Heritage Research, Department of Commerce, Dayanand College, Ajmer - INDIA., 2010)
An adoption of an environmentally friendly management approach is one of the popular issues addressed in many industries including the restaurant industry. This study empirically examines the internal and external drivers and barriers that may contribute to the responsiveness of restaurateurs towards implementation of environmentally friendly practices. Using semi-structured interviews with the independently owned casual upscale restaurants operators, some meaningful insights were obtained. Restaurateurs, perhaps like most individuals are concerned about the environment, but are not fully aware and educated about the present condition of the environment. Inadequate knowledge coupled with intermittent green supply chain has resulted into a half-hearted commitment towards the preservation of the environment. This circumstance indicates that in order for significant effort cannot be shouldered solely by responsible authorities. The business community, corporate or individually owned needs to resume a more active role in fostering environment-friendly practices (EFPs) which in turn can serve as a “win-win” situation for all parties.